P450 Prep use, STD acquisition and sexual risk behavior. (14th July 2019) - Burrell, Amy; Tilchin, Carla; Ruhs, Sebastian; Schumacher, Christina; Fields, Errol; Wagner, Jessica; Greenbaum, Adena; Jennings, Jacky
Abstract : Background: Some studies have shown an association between HIV pre-exposure prophylaxis (PrEP) use, STD acquisition and increased sexual risk behaviors (e.g. condomless sex). The objective was to determine the association between PrEP use, STD infection (i.e. syphilis, gonorrhea, chlamydia) and sexual risk behaviors (i.e. condomless sex, sex partner concurrency) in one mid-Atlantic city with an established epidemic of HIV. Methods: Data came from the Understanding Sexual Health in Networks Study (USHINE), an ongoing longitudinal cohort study of MSM between the ages of 18–45. Participants completed an egocentric sexual network survey. Summary statistics, chi-squared tests, and t-tests were used for hypothesis testing. Results: 173 men completed the sexual network survey. 52 (30.1%) men were HIV uninfected and 52 (30.1%) men reported PrEP use. PrEP users (vs non-users) were less likely to be positive for syphilis (10.6% vs 26.8%, p=0.03), but no more likely to be positive for gonorrhea (15.4% vs 8.0%, p=0.25) or chlamydia (17.3% vs 16.0%, p= 0.86). PrEP users (vs non-users) were more likely to report condomless sex (88.5% vs 69.2%, p =0.02) and sex partner concurrency (57.7% vs 32.7%, p=0.01). Conclusion: PrEP users were less likely to be infected with syphilis and no more likely than non-PrEP users to be gonorrhea and chlamydia infected. PrEP users were more likely to report sexual risk behaviors including condomless sex and sex partner concurrency compared to non-PrEP users. The increased sexual risk behaviors among PrEP users is concerning and emphasizes the importance of prevention messaging for PrEP users. Disclosure: No significant relationships.